Ecological niche modeling of diploid flowering rush (Butomus umbellatus L.) in the United States - Maxwell G. Gebhart; Ryan M. Wersal (Journal of Freshwater Ecology)
Flowering rush (Butomus umbellatus L.) is an invasive perennial monocot found along the United States (U.S.).–Canadian border which can grow into large monotypic mats that can cause water use issues. Currently, there are two known cytotypes, diploid and triploid, within the invaded range; however, basic ecological research is lacking on the diploid cytotype. Ecological niche modelling (ENM) was done on three known populations of the diploid cytotype, alongside a global site model, to determine site-specific abiotic influences and potential suitability within the U.S. The ENM was constructed using climatic and soil variables from public sources with resultant models compared to currently known populations of flowering rush throughout the U.S. Diploid flowering rush populations and the global site models were highly reliant on precipitation in the driest month (27–39% model contribution) and one site was highly reliant on precipitation seasonality (38% model contribution). Diploid flowering rush populations in this study displayed different responses towards abiotic factors; however, seasonal signaling of precipitation patterns are highly important. Furthermore, diploid flowering rush is predicted to invade numerous areas with less than suitable habitat which should warrant further monitoring to prevent further spread.